The research progress of perioperative non-pharmacological interventions on postoperative cognitive dysfunction: a narrative review - Zhao, Li; Guo, Yiping; Zhou, Xuelei; Mao, Wei; Zhu, Hongyu; Chen, Linlin; Liu, Xianchun; Zhang, Longyi; Xie, Ying; Li, Linji (Frontiers in Neurology, 2024)
Postoperative cognitive dysfunction (POCD) is a common neurological complication in elderly patients after surgery and general anesthesia. The occurrence of POCD seriously affects the postoperative recovery of patients, and leads to prolonged hospital stay, reduced quality of life, increased medical costs, and even higher mortality. There is no definite and effective drug treatment for POCD. More evidence shows that perioperative non-pharmacological intervention can improve postoperative cognitive function and reduce the incidence of POCD. Therefore, our studies summarize the current non-pharmacological interventions of POCD from the aspects of cognitive training, physical activity, transcutaneous electrical acupoint stimulation, noninvasive brain stimulation, non-pharmacological sleep improvement, music therapy, environment, and multimodal combination Interventions, to provide more data for clinical application and research.